Utilization of high-range water reducing admixture having air-entraining agents in cementitious systems. (1st April 2023) - Şahin, Hatice Gizem; Mardani, Ali; Özen, Süleyman; Emin, Ayvaz
Abstract: Utilization of admixtures with different action mechanisms has increased by combining them both physically and chemically. The effect of the use of modified water reducing admixture having air-entraining agents on the some fresh and hardened state properties of concrete mixtures was investigated in this study. It was determined that the utilization of air-entraining admixtures (AEA) increases the workability of fresh concrete due to the fact that it creates spherical-shaped air bubbles in matrix. However, there are contradictions about the effect of cementitious systems on rheological properties in the literature. Also, compatibility problems may occur when high range water-reducing admixtures (HRWRA) and AEA are used together in mixtures. It was reported that the use of HRWRA causes an increase in the spacing factor and the action performance of the AEA is adversely affected. However, it was understood that limited studies were carried out on increasing the compatibility of these admixtures in the literature. The methods that can be applied to prevent these incompatibilities were evaluated. First, the incompatibility between them can be reduced by optimizing the order of adding the admixtures (HRWRA and AEA) to the mixture. Secondly, it was understood that the use of water-reducing admixtures modified with air-entraining properties in concrete mixtures can eliminate the stated incompatibilities. Highlights: Studied to increase the compatibility of AEA and HRWRA. The incompatibility between HRWRA and AEA can be reduced by optimizing the order. The use of HRWRA modified with AE properties can eliminate the incompatibilities.